Tunnel wind and earthquake resistant coating and preparation method thereof

CN122878787APending Publication Date: 2026-10-09XIAMEN ANLONGDA FIRE-FIGHTING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611172965.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]为了解决涂料层与混凝土基体之间的界面附着力以及涂料层自身的结构强度的问题,本申请提供一种提高隧道抗风震性能涂料及其制备方法

Benefits of technology

1、通过蛭石粉、珍珠岩、漂珠及海泡石等多孔轻质矿物填料的协同复配,在涂层内部形成致密连通的微孔隔热网络,降低导热系数,有效阻隔或减缓火灾高温及极端热环境向混凝土基体的热量传递,降低水泥水化产物的脱水速率,减少热应力累积,从而抑制衬砌结构的开裂、表层剥落及炸裂,保障隧道在高温环境下的结构稳定性与使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of coatings, in particular to a coating for improving the wind and earthquake resistance of a tunnel and a preparation method thereof, which is prepared from the following raw materials in parts by weight: cement 35-40 parts, modified latex 15-20 parts, vermiculite powder 12-15 parts, perlite 6-10 parts, fiber 10-15 parts, floating bead 5-8 parts, sepiolite 4-8 parts, attapulgite powder 2-6 parts, redispersible glue powder 4-6 parts, cellulose nanocrystal 3-5 parts, polyvinyl alcohol 2-4 parts, surfactant 0.2-0.8 parts and other auxiliaries 1-2 parts. Through the above formula, the wind and earthquake resistance, interface adhesion and heat insulation and protection efficiency of the tunnel heat insulation coating are synergistically improved, and the problems that the coating is prone to peeling, cracking and falling under dynamic negative pressure suction in the prior art are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating technology, and more specifically, to a coating for improving the wind and earthquake resistance of tunnels and a method for preparing the same. Background Technology

[0002] The tunnel walls are constantly exposed to a complex and variable thermal environment. Especially during fires or extreme external temperatures, the internal temperature of the concrete structure can rise rapidly in a short period. The main hydration products in the cement matrix, such as hydrated calcium silicate (gel, ettringite, and other silicate minerals), are prone to dehydration and loss of crystal water under high temperatures, leading to significant thermal stress within the concrete. As the temperature continues to rise, this thermal stress accumulates, causing severe damage to the lining structure, including cracking, surface spalling, and even explosion, seriously threatening the structural safety and service life of the tunnel.

[0003] To address the aforementioned high-temperature damage issues, existing technologies typically employ the method of spraying heat-insulating coatings onto the tunnel's inner walls. This creates a protective heat-insulating layer on the concrete surface, blocking or slowing the rate of heat transfer to the concrete matrix, thereby reducing the dehydration rate of silicate minerals and maintaining the structural stability of the concrete in high-temperature environments. However, in practical engineering applications, it has been found that high-speed vehicle traffic within tunnels creates a significant negative pressure zone near the tunnel walls. This negative pressure exerts a continuous dynamic suction effect on the coating layer. The interfacial adhesion between existing heat-insulating coatings and the concrete matrix, as well as the structural strength of the coating layer itself, is insufficient to withstand the repeated action of this dynamic negative pressure, leading to peeling, cracking, and detachment of the coating layer. Once the coating layer detaches, the concrete matrix is ​​directly exposed to the high-temperature environment, resulting in the loss of its heat insulation function and a significant increase in safety hazards.

[0004] Therefore, how to further improve the interfacial adhesion between the coating layer and the concrete substrate and the structural strength of the coating layer itself while ensuring that the thermal insulation coating has good thermal insulation performance, so that it can effectively resist the dynamic negative pressure suction effect generated by the high-speed passage of vehicles in the tunnel and avoid the coating layer peeling off, is a technical problem that urgently needs to be solved in the field of tunnel inner wall thermal insulation and protection technology. Summary of the Invention

[0005] To address the issues of interfacial adhesion between the coating layer and the concrete substrate, as well as the structural strength of the coating layer itself, this application provides a coating for improving the wind and earthquake resistance of tunnels and its preparation method.

[0006] In the first aspect, this application provides a coating for improving the wind and earthquake resistance of tunnels, employing the following technical solution: A coating for improving the wind and earthquake resistance of tunnels is prepared from the following raw materials in parts by weight: 35-40 parts cement 15-20 parts modified latex 12-15 parts vermiculite powder 6-10 parts perlite 10-15 parts fiber 5-8 parts of cling beads 4-8 parts sepiolite 2-6 parts of attapulgite powder 4-6 parts of redispersible polymer powder 3-5 parts of cellulose nanocrystals 2-4 parts of polyvinyl alcohol Surfactant 0.2-0.8 parts Other adjuvants: 1-2 parts.

[0007] By adopting the above technical solutions, the tunnel thermal insulation coating has achieved a synergistic improvement in wind and earthquake resistance, interface adhesion, and thermal insulation performance, effectively solving the problems of peeling, cracking, and detachment of the coating under dynamic negative pressure suction in the existing technology.

[0008] This application utilizes porous lightweight fillers such as vermiculite powder, perlite, cenospheres, and sepiolite to form a dense microporous thermal insulation network. Their low thermal conductivity and high porosity effectively block heat transfer to the concrete matrix, reducing the dehydration rate of cement hydration products at high temperatures, minimizing thermal stress accumulation, and inhibiting lining cracking, spalling, and spalling. Modified latex, redispersible polymer powder, and polyvinyl alcohol penetrate into the micropores of the concrete surface, forming a strong and flexible interfacial transition zone through physical anchoring and chemical action, further enhancing interfacial bonding strength and ensuring the coating remains tightly adhered under periodic dynamic negative pressure. Fibers form a three-dimensional network skeleton within the coating, effectively dispersing negative pressure and thermal stress; cellulose nanocrystals fill micro-defects at the nanoscale, enhancing cohesive strength and toughness. Attapulgite powder, with its layered chain structure and large specific surface area, enhances physical entanglement and support, improving coating density and structural integrity. Cement provides an inorganic mechanical skeleton and refractory properties, forming an organic-inorganic interpenetrating network with the organic bonding system, further improving durability and high-temperature stability. Surfactants and additives improve filler dispersibility and coating application adaptability.

[0009] This coating achieves a combination of high-efficiency heat insulation, high adhesion, and high strength, ensuring that the tunnel wall maintains a long-term stable heat insulation and protection effect under complex high-temperature and dynamic negative pressure coupling conditions.

[0010] Preferably, the modified latex is prepared by the following method: 1) Add water to the reactor, heat to 40-45℃, add sodium dodecyl sulfate and nonylphenol polyoxyethylene ether and stir to dissolve, then add styrene, butyl acrylate, hydroxyethyl acrylate, vinyltriethoxysilane, octamethylcyclotetrasiloxane, acrylic acid and glycidyl methacrylate, stir at high speed to form a uniform pre-emulsion. 2) Add sodium bicarbonate to deionized water to adjust the pH to 7.0-7.5, heat to 75-78℃, add 1 / 10 of the pre-emulsion and 1 / 3 of the initiator, and stir to obtain the seed emulsion; 3) Add pre-emulsion and initiator dropwise to the seed emulsion, controlling the dropwise temperature at 80-82℃. After the dropwise addition is complete, keep the reaction at this temperature for 1.5-2 hours, then cool down to 60-65℃, add the initiator again, and react for 30-45 minutes. Cool down to below 40℃, and adjust the pH to 7.5-8.5 with ammonia water to obtain the modified latex.

[0011] Preferably, the raw materials used to prepare the modified latex are as follows by weight: 15-20 parts of styrene 20-25 parts butyl acrylate 5-8 parts of hydroxyethyl acrylate Vinyltriethoxysilane 3-5 parts 1-3 parts of octamethylcyclotetrasiloxane 1-2 parts acrylic acid 2-3 parts glycidyl methacrylate Sodium dodecyl sulfate 0.8-1 part Nonylphenol polyoxyethylene ether 0.5-0.8 parts Initiator 0.4-0.6 parts 80-100 parts deionized water.

[0012] By employing the above-mentioned technical solution, using styrene and butyl acrylate as the main monomers, and adding functional monomers such as acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, vinyltriethoxysilane, and octamethylcyclotetrasiloxane for multi-component copolymerization, a polymer emulsion with uniform particle size and excellent stability is obtained. The carboxyl, hydroxyl, and epoxy groups introduced by acrylic acid, hydroxyethyl acrylate, and glycidyl methacrylate can enhance the chemical bonding and physical anchoring effect between latex molecules and the concrete substrate surface, significantly improving the adhesion of the coating interface.

[0013] The silanol groups formed after the hydrolysis of vinyltriethoxysilane can undergo a condensation reaction with the hydroxyl groups on the concrete surface, further enhancing the adhesion strength between the coating and the substrate, as well as the coating's cohesion and density. The introduction of octamethylcyclotetrasiloxane endows the latex with excellent heat and weather resistance and hydrophobic properties, effectively improving the coating's thermal stability and anti-aging ability under high-temperature environments. The multifunctional cross-linked structure of styrene and butyl acrylate allows the latex film to maintain high mechanical strength while also possessing good flexibility and impact resistance, effectively adapting to the micro-deformation of the concrete matrix and dissipating stress generated by dynamic negative pressure.

[0014] In summary, this modified latex, as a coating base material, not only endows the coating with excellent flexibility and crack resistance through the synergistic effect of multiple functional groups and organosilicon modification, but also enhances the coating's resistance to dynamic negative pressure suction by forming a strong organic-inorganic composite interface and dense cross-linked network with the concrete matrix, ensuring the integrity and reliability of the thermal insulation protective layer during long-term service.

[0015] Preferably, the surfactant includes one of sulfosuccinates, carboxylates, or polyoxyethylene fatty acid esters.

[0016] By adopting the above technical solution, the surfactant effectively improves the dispersion uniformity of each solid filler in the liquid phase, enhances the wetting performance, leveling and construction adaptability of the coating, and ensures that the coating forms a uniform, dense and defect-free protective coating on the concrete surface.

[0017] Preferably, the length of the fiber is 0.5-5 mm.

[0018] By adopting the above technical solution, the fibers within this length range are uniformly dispersed in the coating and form a three-dimensional network reinforcement skeleton, which improves the tensile strength, toughness and crack resistance of the coating layer, effectively resists the repeated suction of dynamic negative pressure, prevents the coating from peeling, cracking and falling off, and ensures the structural integrity and long-term service reliability of the thermal insulation protection layer of the tunnel inner wall.

[0019] Preferably, the fiber is composed of polyvinyl alcohol fiber, wood fiber and polypropylene fiber in a weight ratio of 5:4-6:1-2.

[0020] By adopting the above technical solution, polyvinyl alcohol fiber provides excellent flexibility and tensile strength, wood fiber enhances the coating cohesion and crack resistance, and polypropylene fiber improves impact resistance and fatigue resistance. The three form a complementary three-dimensional reinforcement network, which effectively disperses the stress generated by dynamic negative pressure, prevents the coating from peeling, cracking and falling off, and ensures the long-term stability of the thermal insulation protective layer.

[0021] Preferably, the vermiculite powder has an average particle size of 20-50 μm, the perlite has an average particle size of 100-200 μm, the cenospheres have an average particle size of 100-150 μm, the sepiolite has an average particle size of 5-50 μm, and the attapulgite powder has an average particle size of 10-25 μm.

[0022] By adopting the above technical solution and optimizing the particle size distribution of vermiculite powder, perlite, cenospheres, sepiolite, and attapulgite powder, large-particle perlite and cenospheres mainly form the thermal insulation skeleton in the coating, medium-particle vermiculite powder effectively fills the intermediate-level voids, and small-particle sepiolite and attapulgite powder further penetrate into the microscopic gaps to achieve tight packing, thereby forming a dense thermal insulation network with multi-level pore size distribution. This optimized gradation not only reduces the thermal conductivity and bulk density of the coating, improving its thermal insulation and flame retardant performance, but also significantly increases the coating's packing density, structural compactness, and cohesive strength, effectively reducing internal defects and stress concentration, and enabling the coating to maintain morphological stability under dynamic negative pressure, making it less prone to cracking and peeling.

[0023] Preferably, the other additives include leveling agents and defoamers.

[0024] By adopting the above technical solutions, the leveling agent improves leveling properties and eliminates brush marks and orange peel; the defoamer eliminates bubbles, prevents pinholes and craters, ensures a dense and uniform coating, and improves adhesion and reliability.

[0025] Secondly, this application provides a method for preparing a coating to improve the wind and earthquake resistance of tunnels, using the following technical solution: A method for preparing a coating to improve the wind and earthquake resistance of tunnels includes the following steps: Cement, modified latex, vermiculite powder, perlite, fiber, cenospheres, sepiolite, attapulgite powder, redispersible polymer powder, cellulose nanocrystals, polyvinyl alcohol, surfactants and other additives are mixed evenly to obtain a coating that improves the wind and earthquake resistance of tunnels.

[0026] By employing the above technical solution, all raw materials are thoroughly mixed to form a highly uniform and stable dispersion system of inorganic thermal insulation fillers, organic binders, and fiber reinforcement materials. This ensures that each functional component is evenly distributed in the coating and works synergistically. The resulting coating has strong application adaptability and can form a uniform, dense, and highly adhesive thermal insulation protective layer on concrete surfaces, effectively guaranteeing the coating's thermal insulation and flame retardant properties, mechanical strength, and resistance to negative pressure.

[0027] In summary, this application has the following beneficial effects: 1. Through the synergistic compounding of porous lightweight mineral fillers such as vermiculite powder, perlite, cenospheres and sepiolite, a dense and interconnected microporous thermal insulation network is formed inside the coating, reducing the thermal conductivity, effectively blocking or slowing down the heat transfer from high temperature fire and extreme thermal environment to the concrete matrix, reducing the dehydration rate of cement hydration products, reducing the accumulation of thermal stress, thereby inhibiting cracking, surface spalling and cracking of the lining structure, and ensuring the structural stability and service life of the tunnel in high temperature environment.

[0028] 2. Through the synergistic effect of modified latex, redispersible adhesive powder, polyvinyl alcohol, fiber, cellulose nanocrystals, attapulgite powder and other components, the interfacial adhesion between the coating layer and the concrete substrate is improved, as well as the coating's own cohesion, density, toughness and mechanical strength. This forms a strong organic-inorganic composite reinforcement structure, which enables the coating to effectively resist the repeated suction effect of dynamic negative pressure generated near the wall surface when vehicles pass at high speeds. This reduces the peeling, cracking and detachment of the coating layer, ensuring the long-term reliability of the thermal insulation and protection function of the tunnel wall and the structural safety. Detailed Implementation Preparation Example 1 A modified latex is prepared by the following method: 1) Add 6 kg of water to the reactor, heat to 40°C, add 0.09 kg of sodium dodecyl sulfate and 0.07 kg of nonylphenol polyoxyethylene ether (TX-40) and stir to dissolve. Then add 1.8 kg of styrene, 2.3 kg of butyl acrylate, 0.7 kg of hydroxyethyl acrylate, 0.4 kg of vinyltriethoxysilane, 0.2 kg of octamethylcyclotetrasiloxane, 0.15 kg of acrylic acid and 0.25 kg of glycidyl methacrylate. Stir at 1500 rpm to form a uniform pre-emulsion. 2) Add sodium bicarbonate to 3 kg of deionized water to adjust the pH to 7.0, heat to 75°C, add 1 / 10 of the pre-emulsion and 0.015 kg of initiator, and stir to obtain the seed emulsion; 3) Add 0.025 kg of pre-emulsion and initiator to the seed emulsion, with the addition temperature controlled at 80℃. After the addition is complete, keep the reaction at this temperature for 1.5 h, then cool down to 60℃, add 0.001 kg of initiator and react for 30 min. Cool down to below 40℃ and adjust the pH to 7.5 with ammonia water to obtain the modified latex.

[0029] Preparation Example 2 A modified latex is prepared by the following method: 1) Add 6 kg of water to the reactor, heat to 43°C, add 0.08 kg of sodium dodecyl sulfate and 0.05 kg of nonylphenol polyoxyethylene ether (TX-40) and stir to dissolve. Then add 1.5 kg of styrene, 2 kg of butyl acrylate, 0.5 kg of hydroxyethyl acrylate, 0.3 kg of vinyltriethoxysilane, 0.1 kg of octamethylcyclotetrasiloxane, 0.1 kg of acrylic acid and 0.2 kg of glycidyl methacrylate. Stir at 1700 rpm to form a uniform pre-emulsion. 2) Add sodium bicarbonate to 2 kg of deionized water to adjust the pH to 7.3, heat to 77°C, add 1 / 10 of the pre-emulsion and 0.015 kg of initiator, and stir to obtain the seed emulsion; 3) Add 0.035 kg of pre-emulsion and initiator to the seed emulsion, with the addition temperature controlled at 81℃. After the addition is complete, keep the reaction at this temperature for 1.8 h, then cool down to 63℃, add 0.001 kg of initiator and react for 40 min. Cool down to below 40℃ and adjust the pH to 8.0 with ammonia water to obtain the modified latex.

[0030] Preparation Example 3 A modified latex is prepared by the following method: 1) Add 7 kg of water to the reactor, heat to 45°C, add 0.1 kg of sodium dodecyl sulfate and 0.08 kg of nonylphenol polyoxyethylene ether (TX-40) and stir to dissolve. Then add 2 kg of styrene, 2.5 kg of butyl acrylate, 0.8 kg of hydroxyethyl acrylate, 0.5 kg of vinyltriethoxysilane, 0.3 kg of octamethylcyclotetrasiloxane, 0.2 kg of acrylic acid and 0.3 kg of glycidyl methacrylate. Stir at 1800 rpm to form a uniform pre-emulsion. 2) Add sodium bicarbonate to 3 kg of deionized water to adjust the pH to 7.5, heat to 78°C, add 1 / 10 of the pre-emulsion and 0.02 kg of initiator, and stir to obtain the seed emulsion; 3) Add 0.04 kg of pre-emulsion and initiator to the seed emulsion, with the addition temperature controlled at 82℃. After the addition is complete, keep the reaction at this temperature for 2 h, then cool down to 65℃, add 0.002 kg of initiator and react for 45 min. Cool down to below 40℃ and adjust the pH to 8.5 with ammonia water to obtain the modified latex.

[0031] Example Example

[0032] A coating for improving the wind and earthquake resistance of tunnels is prepared by the following method: 35 kg of cement, 15 kg of modified latex from Preparation Example 1, 12 kg of vermiculite powder, 6 kg of perlite, 10 kg of fiber, 5 kg of cenospheres, 4 kg of sepiolite, 2 kg of attapulgite powder, 4 kg of redispersible polymer powder, 3 kg of cellulose nanocrystals, 2 kg of polyvinyl alcohol, 0.2 kg of surfactant, and 1 kg of other additives (0.5 kg of leveling agent BYK-378 and 0.5 kg of defoamer BYK-555) were mixed evenly to obtain a coating that improves the wind and earthquake resistance of tunnels.

[0033] The fiber length is 0.5 mm.

[0034] The fiber is composed of polyvinyl alcohol fiber, wood fiber and polypropylene fiber in a weight ratio of 5:4:1.

[0035] The average particle size of vermiculite powder is 20 μm, that of perlite is 100 μm, that of cenospheres is 100 μm, that of sepiolite is 5 μm, and that of attapulgite powder is 10 μm.

[0036] Example 2 A coating for improving the wind and earthquake resistance of tunnels is prepared by the following method: 38 kg of cement, 18 kg of modified latex from Preparation Example 2, 14 kg of vermiculite powder, 8 kg of perlite, 12 kg of fiber, 7 kg of cenospheres, 6 kg of sepiolite, 4 kg of attapulgite powder, 5 kg of redispersible polymer powder, 4 kg of cellulose nanocrystals, 3 kg of polyvinyl alcohol, 0.6 kg of surfactant, and 1.5 kg of other additives (1 kg of leveling agent BYK-378 and 0.5 kg of defoamer BYK-555) were mixed evenly to obtain a coating that improves the wind and earthquake resistance of tunnels.

[0037] The fiber length is 3mm.

[0038] The fiber is composed of polyvinyl alcohol fiber, wood fiber and polypropylene fiber in a weight ratio of 5:5:1.5.

[0039] The average particle size of vermiculite powder is 40 μm, that of perlite is 150 μm, that of cenospheres is 130 μm, that of sepiolite is 30 μm, and that of attapulgite powder is 15 μm.

[0040] Example 3 A coating for improving the wind and earthquake resistance of tunnels is prepared by the following method: 40 kg of cement, 20 kg of modified latex from Preparation Example 3, 15 kg of vermiculite powder, 10 kg of perlite, 15 kg of fiber, 8 kg of cenospheres, 8 kg of sepiolite, 6 kg of attapulgite powder, 6 kg of redispersible polymer powder, 5 kg of cellulose nanocrystals, 4 kg of polyvinyl alcohol, 0.8 kg of surfactant, and 2 kg of other additives (1 kg of leveling agent BYK-378 and 1 kg of defoamer BYK-555) were mixed evenly to obtain a coating that improves the wind and earthquake resistance of tunnels.

[0041] The fiber length is 5mm.

[0042] The fiber is composed of polyvinyl alcohol fiber, wood fiber and polypropylene fiber in a weight ratio of 5:6:2.

[0043] The average particle size of vermiculite powder is 50 μm, that of perlite is 200 μm, that of cenospheres is 150 μm, that of sepiolite is 50 μm, and that of attapulgite powder is 25 μm.

[0044] Example 4 A coating for improving the wind and earthquake resistance of tunnels. The difference between this embodiment and Embodiment 1 is that the fiber is composed of wood fiber and polypropylene fiber in a weight ratio of 4:1.

[0045] Example 5 A coating for improving the wind and earthquake resistance of tunnels. The difference between this embodiment and Embodiment 1 is that the fiber is polypropylene fiber.

[0046] Example 6 A coating for improving the wind and earthquake resistance of tunnels. The difference between this embodiment and Embodiment 1 is that the fiber length is 10mm.

[0047] Example 7 A coating for improving the wind and earthquake resistance of tunnels. The difference between this embodiment and Embodiment 1 is that the average particle size of vermiculite powder is 20 μm, the average particle size of perlite is 20 μm, the average particle size of cenospheres is 20 μm, the average particle size of sepiolite is 20 μm, and the average particle size of attapulgite powder is 20 μm.

[0048] Example 8 A coating for improving the wind and earthquake resistance of tunnels. The difference between this embodiment and Example 1 is that the following are included: 38 kg of cement, 16 kg of modified latex from Preparation Example 1, 13 kg of vermiculite powder, 7 kg of perlite, 10 kg of fiber, 5 kg of cenospheres, 4 kg of sepiolite, 4 kg of attapulgite powder, 6 kg of redispersible polymer powder, 5 kg of cellulose nanocrystals, 4 kg of polyvinyl alcohol, 0.2 kg of surfactant, and 1 kg of other additives (0.5 kg of leveling agent BYK-378 and 0.5 kg of defoamer BYK-555).

[0049] Comparative Example Comparative Example 1 A coating for improving the wind and earthquake resistance of tunnels. The difference between this comparative example and Example 1 is that the modified latex is replaced with an equal weight of deionized water.

[0050] Comparative Example 2 A coating for improving the wind and earthquake resistance of tunnels. The difference between this comparative example and Example 1 is that the modified latex is replaced with an equal weight of ordinary styrene-acrylic latex.

[0051] Ordinary styrene-acrylic latex has a solids content of 45%, a viscosity of 80 mPa.s, a pH value of approximately 8, and is commercially available.

[0052] Comparative Example 3 A coating for improving the wind and earthquake resistance of tunnels. The difference between this comparative example and Example 1 is that cellulose nanocrystals are not added.

[0053] Comparative Example 4 A coating for improving the wind and earthquake resistance of tunnels. The difference between this comparative example and Example 1 is that no fibers are added.

[0054] Comparative Example 5 A coating for improving the wind and earthquake resistance of tunnels. The difference between this comparative example and Example 1 is that 23 kg of heavy calcium carbonate replaces vermiculite, perlite and cenospheres.

[0055] Detection methods / test methods Bond strength: Tested according to GB28375-2025; Fire resistance performance: tested according to GB28375-2025; Vibration resistance performance: Tested according to GB28375-2025. Experimental data are shown in Table 1: Table 1. Experimental data of Examples 1-8 and Comparative Examples 1-5

[0056] The experimental data above show that the synergistic effect of modified latex, multi-graded porous insulating filler, three fiber systems, and cellulose nanocrystals in the tunnel insulation coating achieves a synergistic improvement in bonding strength, fire resistance, and vibration resistance. The bonding strength of Examples 1-8 before freeze-thaw cycles reached 0.30-0.58 MPa, and after 15 freeze-thaw cycles, it remained at 0.22-0.51 MPa, both significantly higher than the ≥0.15 MPa limit specified in GB 28375-2025. The fire resistance, with a coating thickness of approximately 20 mm, reached Fp2.28-Fp2.72 h, better than the standard requirement of Fp2.00 h. The vibration resistance (bonding strength after 120 min of vibration) reached 0.22-0.52 MPa, also meeting the standard requirement of ≥0.15 MPa.

[0057] By comparing Example 1 with Comparative Examples 1-5, it can be seen that this application achieves a synergistic improvement in the bonding strength, fire resistance and wind and earthquake resistance of tunnel coatings through the multi-element synergy of modified latex, cellulose nanocrystals, ternary fiber system and multi-graded porous heat insulation filler.

[0058] Comparing Examples 1 and 4-7, it is evident that optimizing the gradation and type of vermiculite powder, perlite, cenospheres, sepiolite, and attapulgite powder forms a good thermal insulation network, thereby improving its fire resistance performance.

[0059] Comparing Examples 1 and 8, it is shown that optimizing the dosage in the formulation further improves the bonding strength, fire resistance, and wind and earthquake resistance of the tunnel coating.

[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A coating for improving the wind and earthquake resistance of tunnels, characterized in that, It is prepared from the following raw materials in parts by weight: 35-40 parts cement 15-20 parts modified latex 12-15 parts vermiculite powder 6-10 parts perlite 10-15 parts fiber 5-8 parts of cling beads 4-8 parts sepiolite 2-6 parts of attapulgite powder 4-6 parts of redispersible polymer powder 3-5 parts of cellulose nanocrystals 2-4 parts of polyvinyl alcohol Surfactant 0.2-0.8 parts Other adjuvants: 1-2 parts.

2. The coating for improving the wind and earthquake resistance of tunnels according to claim 1, characterized in that, The modified latex is prepared by the following method: 1) Add water to the reactor, heat to 40-45℃, add sodium dodecyl sulfate and nonylphenol polyoxyethylene ether and stir to dissolve, then add styrene, butyl acrylate, hydroxyethyl acrylate, vinyltriethoxysilane, octamethylcyclotetrasiloxane, acrylic acid and glycidyl methacrylate, stir at high speed to form a uniform pre-emulsion. 2) Add sodium bicarbonate to deionized water to adjust the pH to 7.0-7.5, heat to 75-78℃, add 1 / 10 of the pre-emulsion and 1 / 3 of the initiator, and stir to obtain the seed emulsion; 3) Add pre-emulsion and initiator dropwise to the seed emulsion, controlling the dropwise temperature at 80-82℃. After the dropwise addition is complete, keep the reaction at this temperature for 1.5-2 hours, then cool down to 60-65℃, add the initiator again, and react for 30-45 minutes. Cool down to below 40℃, and adjust the pH to 7.5-8.5 with ammonia water to obtain the modified latex.

3. The coating for improving the wind and earthquake resistance of tunnels according to claim 2, characterized in that, The raw materials used to prepare the modified latex are as follows (parts by weight): 15-20 parts of styrene 20-25 parts butyl acrylate 5-8 parts of hydroxyethyl acrylate Vinyltriethoxysilane 3-5 parts 1-3 parts of octamethylcyclotetrasiloxane 1-2 parts acrylic acid 2-3 parts glycidyl methacrylate Sodium dodecyl sulfate 0.8-1 part Nonylphenol polyoxyethylene ether 0.5-0.8 parts Initiator 0.4-0.6 parts 80-100 parts deionized water.

4. The coating for improving the wind and earthquake resistance of tunnels according to claim 2, characterized in that: The initiator is potassium persulfate or sodium persulfate.

5. The coating for improving the wind and earthquake resistance of tunnels according to claim 4, characterized in that: The surfactant includes one of sulfosuccinates, carboxylates, or polyoxyethylene fatty acid esters.

6. The coating for improving the wind and earthquake resistance of tunnels according to claim 4, characterized in that: The fiber has a length of 0.5-5 mm.

7. The coating for improving the wind and earthquake resistance of tunnels according to claim 1, characterized in that: The fiber is composed of polyvinyl alcohol fiber, wood fiber and polypropylene fiber in a weight ratio of 5:4-6:1-2.

8. The coating for improving the wind and earthquake resistance of tunnels according to claim 1, characterized in that: The vermiculite powder has an average particle size of 20-50 μm, the perlite has an average particle size of 100-200 μm, the cenospheres have an average particle size of 100-150 μm, the sepiolite has an average particle size of 5-50 μm, and the attapulgite powder has an average particle size of 10-25 μm.

9. The coating for improving the wind and earthquake resistance of tunnels according to claim 1, characterized in that: The other additives include leveling agents and defoamers.

10. A method for preparing a coating for improving the wind and earthquake resistance of tunnels as described in any one of claims 1-7, characterized in that, Includes the following steps: Cement, modified latex, vermiculite powder, perlite, fiber, cenospheres, sepiolite, attapulgite powder, redispersible polymer powder, cellulose nanocrystals, polyvinyl alcohol, surfactants and other additives are mixed evenly to obtain a coating that improves the wind and earthquake resistance of tunnels.